Study on performance and fractal characteristics of high-strength manufactured sand concrete with different MB values - Zhou, Hailong; Ge, Chenglong; Chen, Yan; Song, Xingfang (Frontiers in Earth Science, 2023)
The mud powder in the manufactured sand (MS) will have an influence on the indicators of the manufactured sand concrete (MSC), and the MB value can quantitatively indicate the mud powder content. To demonstrate the impact of MB values on the performance and microstructural characteristics of the MSC, the paper designed five high-strength MSC proportions at five MB values by controlling the clay powder content. On this basis, the workability, chloride migration coefficient, relative dynamic modulus of elasticity (P), mass loss rate (η), and dry shrinkage rate of MSC concrete were tested under five mix ratios, and the relationship between concrete microstructure, fractal characteristics, and compressive strength (fcc) was analyzed by combining SEM technology and fractal theory. The experiment showed that: the higher the MB, the lower the fluidity of the MSC, and the cohesiveness gradually increases, while the water retention remains basically unchanged. In addition, the chloride migration coefficient gradually increases, the P after 300 freeze-thaw cycles first increases and then gradually decreases, while the η and drying shrinkage first decreases and then gradually increases, and the MB value corresponding to the turning point of these three changes are all 1.10. With MB values of 0.85 and 1.10, the degree of hydration of MSC is higher and the overall structural compactness is better. The higher the MB value, the more inadequate the hydration of concrete, and the mineral components such as fly ash that have not been hydrated inside gradually increase, which leads to the gradual decrease of the overall structure compactness. In addition, when the MB value is small, the SEM image texture of concrete is relatively simple, the fractal dimension value is small, and the corresponding fcc is large. When the MB value is large, the texture of the SEM image is complex, the fractal dimension is large, and the corresponding fcc is small.